2022
DOI: 10.3389/fpls.2022.966339
|View full text |Cite
|
Sign up to set email alerts
|

Delineating meta-quantitative trait loci for anthracnose resistance in common bean (Phaseolus vulgaris L.)

Abstract: Anthracnose, caused by the fungus Colletotrichum lindemuthianum, is one of the devastating disease affecting common bean production and productivity worldwide. Several quantitative trait loci (QTLs) for anthracnose resistance have been identified. In order to make use of these QTLs in common bean breeding programs, a detailed meta-QTL (MQTL) analysis has been conducted. For the MQTL analysis, 92 QTLs related to anthracnose disease reported in 18 different earlier studies involving 16 mapping populations were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 96 publications
1
19
0
1
Order By: Relevance
“…MQTL analysis can detect stable QTLs regardless of their genetic background, chronology and location in the corresponding original investigation [ 16 , 26 , 30 , 96 ]. In comparison to the MQTLs reported in the previous study on white mold [ 13 ] and anthracnose [ 20 ], we identified one further overlapping MQTL named MQTL7P.1 located on chromosome 7 conveying resistance against white mold disease. Four MQTLs (MQTL1P.1, MQTL5P.1, MQTL7P.1, MQTL8P.1) in our study overlapped with five MQTLs of anthracnose disease [ 20 ], three of which located at the closest region to previous study.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…MQTL analysis can detect stable QTLs regardless of their genetic background, chronology and location in the corresponding original investigation [ 16 , 26 , 30 , 96 ]. In comparison to the MQTLs reported in the previous study on white mold [ 13 ] and anthracnose [ 20 ], we identified one further overlapping MQTL named MQTL7P.1 located on chromosome 7 conveying resistance against white mold disease. Four MQTLs (MQTL1P.1, MQTL5P.1, MQTL7P.1, MQTL8P.1) in our study overlapped with five MQTLs of anthracnose disease [ 20 ], three of which located at the closest region to previous study.…”
Section: Discussionmentioning
confidence: 74%
“…In comparison to the MQTLs reported in the previous study on white mold [ 13 ] and anthracnose [ 20 ], we identified one further overlapping MQTL named MQTL7P.1 located on chromosome 7 conveying resistance against white mold disease. Four MQTLs (MQTL1P.1, MQTL5P.1, MQTL7P.1, MQTL8P.1) in our study overlapped with five MQTLs of anthracnose disease [ 20 ], three of which located at the closest region to previous study. Furthermore, four MQTLs including MQTL2P.1, MQTL5P.1, MQTL8P.1, MQTL9P.1 located at the same regions with the hotspot of QTLs in previous study on anthracnose [ 20 ].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations